Implementasi Metode Klasifikasi Bayes Untuk Penentuan Keaslian Madu Lebah Berbasis Embedded System - Ardiansyah Ardiansyah; Dahnial Syauqy; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Honey is a natural substance of the bees that carry a result plant secretions become flower's nectar. Bees are conserved with special care, will produce honey in a good quality. The benefits of honey are for health, beauty and food. We need a lot of time and cost to get honey in a good quality. Moreover, there are many honey's producer have mixed another ingredients like glucose, fluctose in pure honey to get a lot of profit income. The forgery of natural honey often did by seller. Therefore, technology needed to help society for testing authenticity of honey directly and quickly. To minimize these problems, this research has been designed a tool that can check the degree of authenticity of honey bees. In this research using some components that is Bayes methods or commonly called Bayessian Classification. Bayes method is one of method that can be used for processing inconsistent data and bias character. The function of color sensor TCS3200 is for checking the color of honey has been detected. Photodiode is an electronic device of semiconductor material that can be convert the light intensity in electric current, and pH sensors is a sensor that can measure the level of acidity accurately . Based on the results of testing accuracy, the level accuracy of clarification bayes method for honey's authenticity are 88,89%. While, the estimatin speed of time for processing system bayes methode to authenticity of honey has a speed average of 96,388ms.